Faktor Penentu Loyalitas Pasien di Rumah Sakit - Utami, Dyah Tri; Ahmad, Hasyim; Hilmy, M Reza (Journal of Hospital Management, 2020)
Patient loyalty has an important role in the operation of a hospital. Patient loyalty is formulated to achieve a number of return visits that have an impact on hospital profitability and stability. The purpose of this study was to examine the effect of Hospital image on patient satisfaction, service quality on patient satisfaction, hospital image on patient loyalty, patient quality on patient loyalty, patient satisfaction with patient loyalty, hospital image of patient loyalty mediated by patient satisfaction. the quality of service to patient loyalty is mediated by the outpatient satisfaction of RS.AN-NISA Tangerang. Hospital image questionnaire, service quality, patient satisfaction, patient loyalty were distributed to 253 respondents who were general patients. Respondents' answers were processed using the Structural Equation Model (SEM) analysis method. The results obtained that Hospital image, service quality has a significant influence on patient satisfaction, service quality has a positive effect on patient satisfaction, and Hospital image, service quality has no effect on patient loyalty mediated by patient satisfaction.Keyword: hospital image, service quality, patient satisfaction, patient loyalty